Сonceptual basis for building a base of models for determining the value of a construction company’s information assets - Izmaylova , O. (Ways to Improve Construction Efficiency, 2023)
An actual area of research in the field of increasing the effectiveness of the functioning of modern information and communication technologies (ICT) is the principles and methods of establishing the value of information assets (IA) in order to effectively choose means of their protection. The object of research of this work is the decision support system (DSPR) for establishing the value of the information asset of the information and communication technologies of the construction company. The purpose of the study is to determine the conceptual foundations of building a base of system models, which would allow creating a flexible dynamic decision support system for the implementation of decision-making processes, having a flexible structure that provides for the possibility of implementing alternative scenarios (options) for establishing the value of information assets. The principles and conceptual foundations of building a base of models, a decision-making support system with a flexible structure, configured for the possibility of implementing alternative scenarios of expert evaluation, depending on the degree of certainty and availability of data, are proposed. As a conceptual basis, the structure of the model base, alternative and scenario modeling of decision-making processes, a classifier of scenario formation conditions, a database of models in the form of a class diagram, a multivariate process model of information technology for establishing the value of information assets in the form of a set of hierarchical process models of alternative network modeling are considered. In the proposed approach, increasing the probability of the obtained results is achieved due to the fact that the user is given the opportunity to choose the most appropriate and effective evaluation scenario, taking into account the goals and objectives of the evaluation, the availability and degree of certainty of the basic data, the existing resource, time and information limitations when making decisions.